Treatment of a Four-Rooted Maxillary Second Molar Detected with Cone-Beam Computed Tomography - Nahid Mohammadzade Akhlaghi; Mahta Fazlyab (Tehran University of Medical Sciences, 2017)
The significance of clinician's knowledge about root canal anatomy and its possible variations cannot be overlooked. In some cases, taking advantage of complementary imaging techniques can help achieve a perfect flawless endodontic treatment. This article reports endodontic management of a second maxillary molar that had an uncommon anatomy of the chamber floor. After obtaining a cone-beam computed tomography (CBCT) image, the presence of a second palatal root was confirmed. All four roots were treated and patient's symptoms were resolved.